The Theory of Price Determination in Government-Industry Relationships - Agapos, A. M.; Dunlap, Paul R. (Quarterly Journal of Economics, 1970)
Introduction, 85. — The conventional bilateral monopoly, 86. — The government procurement process, 88. — Sole source contracts, 89. — Multisource procurement, 95.